Extended quasiparticle random phase approximation at finite temperatures: calculation of single β-decay Fermi transitions - Civitarese, Enrique Osvaldo (2000)
The formalism of the quasiparticle random phase approximation, extended to include scattering terms in the equation of motion, is used to describe allowed single β-decay transitions of Fermi type at finite temperatures. The calculations were performed by using a realistic single particle basis and a separable two body interaction in the proton-neutron channel. The behavior of the Ikeda sum rule is studied and it is found that this sum rule is strictly conserved in the presence of particle-particle and hole-hole correlations. As an example on the validity of the formalism the case of Fermi transitions in ⁷⁶Ge is considered.